Sociocultural Interactions and Community Education: An Anthropological Study in Indramayu, West Java - Wahid, Dul; Irawan, Feri Indra; Puroman, Eman; Fitri, M. Zein (IAIN Manado, 2025)
This study examines the impact of sociocultural interactions in rural Indramayu on education perspectives, highlighting challenges and opportunities in accessing culturally relevant education. A qualitative descriptive approach was employed in three sub-districts: Kandanghaur, Gabus Wetan, and Bongas, where the majority of residents are farmers and fishermen. Findings suggest that local values, such as cooperation and harmony, influence perceptions of education as a means to enhance livelihoods beyond agriculture and fisheries. However, economic priorities often prevent children from pursuing higher education. Opportunities arise through local wisdom-based education, integrating practical skills and sustainable resource management. Globalization enhances access to knowledge and technology, but it also poses a threat to cultural preservation. This study highlights the importance of striking a balance between technological advancements and the preservation of local cultural values to foster sustainable rural development.